2000
DOI: 10.1002/clc.4960230708
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transient balloon occlusion of the mitral valve on left atrial appendage blood flow velocity and spontaneous echo contrast

Abstract: SummaryBackground: Spontaneous echo contrast (SEC) is a phenomenon that is commonly seen in areas of blood stasis. It is a slowly moving, cloud-like swirling pattern of "smoke" or increased echogenicity recorded on echocardiography. SEC is commonly seen in the left atrium of patients with mitral stenosis or atrial fibrillation. The prescence of SEC has been shown to be a marker of increased thromboembolic risk.Hypothesis: By using transesophageal echocardiography during percutaneous balloon mitral valvotomy (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Upon balloon deflation, LAA blood flow velocity increases again, resulting in the reduction or disappearance of SEC within the same time interval and LAA emptying and filling velocities have increased after the procedure. [23] Basal and postprocedure LAA velocities in patients with atrial fibrillation were found to be lower when compared with velocities in those with sinus rhythm. [23] In the same study at peak balloon inflation, LAA velocities were significantly lower and SEC was significantly higher in a group with atrial fibrillation than in a group with sinus rhythm.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Upon balloon deflation, LAA blood flow velocity increases again, resulting in the reduction or disappearance of SEC within the same time interval and LAA emptying and filling velocities have increased after the procedure. [23] Basal and postprocedure LAA velocities in patients with atrial fibrillation were found to be lower when compared with velocities in those with sinus rhythm. [23] In the same study at peak balloon inflation, LAA velocities were significantly lower and SEC was significantly higher in a group with atrial fibrillation than in a group with sinus rhythm.…”
Section: Discussionmentioning
confidence: 88%
“…[23] Basal and postprocedure LAA velocities in patients with atrial fibrillation were found to be lower when compared with velocities in those with sinus rhythm. [23] In the same study at peak balloon inflation, LAA velocities were significantly lower and SEC was significantly higher in a group with atrial fibrillation than in a group with sinus rhythm. Thus, regular contraction in sinus rhythm may decrease SEC formation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Spontaneous echo contrast within the cardiac chambers or vessels is associated with increased risk of thromboembolism. Left atrial spontaneous echo correlates with low emptying velocity in the left atrial appendage (depressed atrial function) and enlarged left atrium 1,2 . In dilated and akinetic left ventricles SEC may be a precursor of thrombus formation 3,4 …”
Section: Discussionmentioning
confidence: 99%
“…Left atrial spontaneous echo correlates with low emptying velocity in the left atrial appendage (depressed atrial function) and enlarged left atrium. 1,2 In dilated and akinetic left ventricles SEC may be a precursor of thrombus formation. 3,4 Spontaneous echo contrast in the thoracic aorta has been associated with significant aortic atherosclerosis, dilated or aneurysmatic aortas, older age, and low blood velocity.…”
Section: Discussionmentioning
confidence: 99%